The effect of using Arabic calligraphy on contemporary architectural composition (Function-form) - سلطان ليلاس; قصاب أحمد سعيد; معلا سوسن (Latakia University Journal -Engineering Sciences Series, 2022)
The form of Arabic calligraphy with its various forms (naskh, thuluth, kufi, al-Raq’i, al-Diwani, etc.) is one of the most important vocabularies of life in all fields, including the architecture field (where it competed with decoration, sometimes outperformed it and lost with it at other times). In terms of influence and weight in the architectural composition in general and the facades in particular, without ignoring the weight of the overall lines over the ages in showing and beautifying the details of internal and external architecture. Knowing that when studying successive Islamic civilizations, we find great creativity in using and adapting calligraphy of all kinds and forms (and with the differentiation of the materials used (in the formal solution in general). In our research, it was necessary to address the work system between the line on the one hand and the (stable) mass on the other... The goal of this relationship in terms of (proportion, function, rhythm, equilibrium) as areas of line movement on the interface, not to mention the main goal which is the harmony of all of the above with beauty.